Topological insulating phases from two-dimensional nodal loop semimetals - Li, Linhu (2016)
Starting from a minimal model for a two-dimensional nodal loop semimetal, we study the effect of chiral mass gap terms. The resulting Dirac loop anomalous Hall insulator’s Chern number is the phase-winding number of the mass gap terms on the loop.We provide simple lattice models, analyze the topological phases, and generalize a previous index characterizing topological transitions. The responses of the Dirac loop anomalous Hall and quantum spin Hall insulators to a magnetic field’s vector potential are also studied both in weak- and strong-field regimes, as well as the edge states in a ribbon geometry.